Human Rights and Parliamentary Sovereignty in New Zealand - Butler, Petra (Victoria University of Wellington Law Review, 2004)
The paper examines whether there was any basis for Parliament to enact section 3(2) of the Supreme Court Act 2003 in regard to human rights decisions of the Court of Appeal. The paper asks whether the Court of Appeal has indeed been "activist" in its human rights decisions. The discussion focuses on the areas where judicial activism might be suspected, firstly the filling of legislative gaps, and secondly statutory interpretation, with a special focus on implied repeal. Relevant decisions of the House of Lords under the Human Rights Act 1998 (UK) are used as a contrast to the decisions of the New Zealand Court of Appeal. The paper comes to the conclusion that the New Zealand Court of Appeal has not been activist in the area of human rights.